Analisis Biaya Relevan Dalam Pengambilan Keputusan (Memproduksi Sendiri Atau Membeli Dari Luar) Toko Oleh-Oleh Sari Rasa Jember - Khusna, Khanifatul; Hilman Kafi, Dzafierul; Mirzania, Alif; Fauziyyah, Salma (PT. Karya Inovatif Nusantara, 2024)
Information about relevant costs is an important thing that companies always need in making the right decisions. One of the main factors in the failure experienced by a company is management errors in making decisions. The aim of this research is to analyse decision making (produce yourself or buy from outside) of the Sari Rasa Jember Souvenir Shop. This type of research is quantitative descriptive. Data collection methods used in this research include interview and observation methods. The analysis method used is relevant cost analysis. The results of the analysis show that companies must make their own semi-finished products because they can provide cost savings which usually increase company profits compared to companies having to buy semi-finished products from other parties. Suggestions to company management are that companies should apply relevant costs in making decisions to make their own or buy semi-finished products in calculating relevant costs.